Compact modelling and SPICE simulation for three-dimensional, inkjet-printed organic transistors, inverters and ring oscillators. (20th August 2019) - Jung, Sungyeop; Kwon, Jimin; Tokito, Shizuo; Horowitz, Gilles; Bonnassieux, Yvan; Jung, Sungjune
Abstract: We report an in-depth study of three-dimensional (3D) inkjet-printed flexible organic field-effect transistors (FETs) and integrated circuits (ICs), and demonstrate the necessity, the feasibility and the key aspects of modelling-driven design and analysis. In particular, we performed compact modelling of the flexible printed organic FETs to determine transistor parameters from measured electrical characteristics, and to optimize the design of transistors for a balanced inverter. We also conducted a SPICE simulation of both static and dynamic behaviours of flexible printed organic complementary inverters and ring oscillators. This study revealed design rules to guide fabrication of the 3D structure of the inverter. The study also showed that the parasitic capacitances are dominant factors that determine the transient behaviour of the ring oscillator. Our work provides insights that can guide further improvement of flexible printed organic FETs and ICs towards the realisation of increasingly complex organic ICs and unconventional electronic applications.